A modified nanocomposite biosensor for quantitative l-glutamate detection in beef. (October 2020) - Wang, Xiaodan; Duan, Jinjiao; Cai, Yingming; Liu, Dengyong; Li, Xing; Dong, Yanli; Hu, Feng
Abstract: A new biosensor for detecting l -glutamate (l -Glu) in beef was developed. Firstly, a bare Au electrode was surface-modified by gold nanoparticles (Au NPs), graphene oxide (GO), and chitosan (CS) as immobilized materials, and then its surface was connected with l -glutamate oxidase (GluOx). The modified Au NPs/GO/CS electrode was characterized by scanning electron microscopy, and the formation mechanism was elaborated. The response current of the l -Glu biosensor maximized to 0.08 mA at pH 7.5 and 0.09 mA at 30 °C, with a detection range of 0.2–1.4 mM and a detection limit of 0.023 mM. The l -Glu biosensor had high accuracy, and its results linearly fitted with those of the amino acid analyzer with a coefficient of 0.996. The l -Glu biosensor had high selectivity, repeatability, and stability and detected higher l -Glu content in the cooked beef than in the raw beef.